NATO and the United States the enduring alliance - Kaplan, Lawrence S. 1924- (Twayne, 1994)
The North American Treaty Organization (NATO) remains the indispensable link that binds America and Europe in common defense - even after the fall of communism in the former Soviet Union and its satellite countries. The North Atlantic Treaty, which established NATO after its signing in Washington, D.C., in 1949, was one of the West's primary cold war-era countermeasures against the threat of Soviet aggression. Considering a military attack on any member an attack on all its members, NATO has made its way through some 45 years of turbulence from both without and within - the Korean War (1950-53), the Soviet launching of Sputnik in 1957, the erection of the Berlin Wall in 1961, France's sudden withdrawal from the alliance in 1966 and the subsequent relocation of NATO headquarters to Brussels, SALT and START negotiations, the disintegration of the Soviet Union, the reunification of Germany, and the civil war in the former Yugoslavia
Keywords: NATO; North Atlantic Treaty Organization; Bondgenootschappen; Militaire samenwerking; NAVO; USA; United States -- Military policy